STUDI PENGARUH VARIABEL-VARIABEL DALAM CFD UNTUK MENGHITUNG KOEFISIEN TAHANAN KAPAL - Chrismianto, Deddy; Manik, Parlindungan (Diponegoro University, 2013)
Commonly, the Computational Fluid Dynamic (CFD) analysis using the finite volume method, solid modeling is usually used in the early stage in order to prepare a mesh process before the computational process is executed. In this paper the CFD analysis must be executed to obtain a resistance coefficient value, and the verification should be done to ensure a result is close to experimental data. In the CFD analysis, some parameters have been taken into account, including the variation of domain dimensions, variation of mesh sizes, and variation of boundary conditions, in which the comparison between the numerical analysis and experimental data showed good agreement in general. The result of the case no.1 has a smaller difference of the resistance coefficients to the experimental data than other cases, in which the total resistance coefficient (Ct) has a difference about 1.95% of experimental data, the friction resistance (Cf) has a difference about 0.83% of experimental data, and there is a difference about 6.30% of experimental data for the residual resistance (Cr).